Optimisation Of Quality Assurance Programme (Qap) For Image-Guided Adaptive Radiotherapy (Igart) - Sakaria, Kasmayanti (2019)
Image-guided adaptive radiotherapy (IGART) is an advanced radiotherapy treatment technique that involves treatment plan modifications during the treatment course to account for temporal changes in tumour volume. The purpose of this study is to develop a Quality Assurance Programme (QAP) for a linac that is optimised for IGART. The linac investigated in this study is an Elekta Synergy linac with 80 pairs of multileaf collimators (MLC) and cone beam computed tomography (CBCT) image guidance system. An optimised QAP was developed to assess relevant linac performance parameters including dose output delivery, dynamic MLC and CBCT image guidance system. Linac dose output was measured daily using a cross-calibrated detector, Quickcheck. The parameters evaluated were central dose output, beam flatness, beam symmetry and beam quality for a period of 19 months. The variations of measurement were within the tolerance level. The central dose outputs are within ± 2%, the beam flatness results are within ± 1.5%, the beam symmetry results are within ± 3% and the beam quality results are within ± 3%. The dynamic MLC performance was analysed weekly in term of leaf positional accuracy using Elekta’s propriety MLC tracking system that is verified against EPID measurement. The MLC position errors tracked were between -0.30 mm to 0.80 mm, within the range of the results from EPID. The performance of CBCT image guidance system was assessed monthly in term of image quality and CT number accuracy using smaller sized CIRS 062QA and compared against the more commonly used Catphan 600. The interphantom variations were observed in the measured parameters, yet they have similar trend to each other.